Spectroscopy and chromatography characterization of curcumin extracted from the rhizome of turmeric crops in the department of Quindío (Colombia) (Revista de Investigaciones Universidad del Quindío, 2009)
The extraction of natural compounds is one of the fastest growing industries due to the benefits they have compared to their synthetic analogs. In this investigation, the curcumin was extracted from the rhizome of turmeric (Curcuma longa L.) with a yield of 7.03% after 9 hours of extraction using soxhlet extractors with organic solvents (hexane and ethanol). The separation and purification was performed by thin layer and column chromatography using a mixture of chloroform and ethyl acetate as mobile phase. The curcumin was characterized by spectroscopic analysis of ultraviolet visible (UV-Vis), infrared (IR), nuclear magnetic resonance (NMR-1D and 2D-NMR) and mass spectroscopy (MS). The results of the physicochemical analysis of moisture, ashes, ether extract, fiber content and curcumin content from the rhizomes in the region were compared with reports from other regions of the world, finding significant differences between the parameters compared.
Keywords: Curcuma longa Linn; turmeric; curcumin; soxhlet extraction; chromatography